Pemolisian di Era Globalisme: Analisis Faktor Perubahan Lingkungan Ekonomi dan Perkembangan Terorisme - Sonta, Ahrie (Pusat Kajian Keamanan Nasional (Puskamnas) Universitas Bhayangkara Jakarta Raya, 2017)
Policing is one of the final filter mechanisms in order to avoid the impact of globalization in Indonesia. Good policing can anticipate the dynamic of a strategic environment before a bad impact happens in society. Therefore, it is important for police to be able to conduct analyses on comprehensive strategic policing based on sectorial. For example, globalization, economy, and terrorism have specific chains and/or relationship patterns, in which the development influences the livelihood of Indonesian society. Indonesia Police have the role of protecting, assisting, and serving society by giving priority to preventive functions before negative impacts caused by the changes in the strategic environment occur. National strategic analysis is important to develop police capability by using the humanity approach. This essay is to strategically analyze the comprehensive security through the economic point of view including in the context of terrorism.